Pengaruh Dual Skema Pembiayaan Syariah Terhadap Stabilitas Keuangan Bank: Fokus Pada Bank JII - Hakim, Lukman (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
This study aims to analyze the influence of two Islamic financing schemes, murabahah and mudharabah, on the financial stability of Islamic banks listed in the Jakarta Islamic Index (JII) during the 2019–2023 period. A quantitative approach was employed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) method via SmartPLS version 4. Data were collected from the financial reports of three major Islamic banks: Bank Syariah Indonesia (BRIS), Bank BTPN Syariah (BTPS), and Bank Panin Dubai Syariah (PNBS). Financial stability indicators were measured using Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and operational efficiency ratio (BOPO). The results reveal that both murabahah and mudharabah financing schemes significantly and positively affect CAR, NPF, and BOPO. Murabahah financing shows a stronger impact compared to mudharabah in strengthening capital, reducing financing risk, and improving operational efficiency. These findings suggest that optimizing the use of both financing schemes, especially murabahah, contributes to enhancing the financial stability of Islamic banks.